HDAC3 Inhibitor RGFP966 Modulates Neuronal Memory for Vocal Communication Signals in a Songbird Model - Phan, Mimi L.; Gergues, Mark M.; Mahidadia, Shafali; Jimenez-Castillo, Jorge; Vicario, David S.; Bieszczad, Kasia M. (Frontiers in Systems Neuroscience, 2017)
Epigenetic mechanisms that modify chromatin conformation have recently been under investigation for their contributions to learning and the formation of memory. For example, the role of enzymes involved in histone acetylation are studied in the formation of long-lasting memories because memory consolidation requires gene expression events that are facilitated by an open state of chromatin. We recently proposed that epigenetic events may control the entry of specific sensory features into long-term memory by enabling transcription-mediated neuronal plasticity in sensory brain areas. Histone deacetylases, like HDAC3, may thereby regulate the specific sensory information that is captured for entry into long-term memory stores (Phan & Bieszczad 2016). To test this hypothesis, we used an HDAC3-selective inhibitor (RGFP966) to determine whether its application after an experience with a sound stimulus with unique acoustic features could contribute to the formation of a memory that would assist in mediating its later recognition. We gave adult male zebra finches limited exposure to unique conspecific songs (20 repetitions each, well below the normal threshold to form long-term memory), followed by treatment with RGFP966 or vehicle. In different groups, we either made multi-electrode recordings in the higher auditory area NCM (caudal medial nidopallidum), or determined expression of an immediate early gene, zenk (also identified as zif268, egr-1, ngfi-a and krox24), known to participate in neuronal memory in this system. We found that birds treated with RGFP966 showed neuronal memory after only limited exposure, while birds treated with vehicle did not. Strikingly, evidence of neuronal memory in NCM induced by HDAC3-inhibition was lateralized to the left-hemisphere, consistent with our finding that RGFP966-treatment also elevated zenk expression only in the left hemisphere. The present findings show feasibility for epigenetic mechanisms to control neural plasticity underlying the formation of specific memories for conspecific communication sounds This is the first evidence in zebra finches that epigenetic mechanisms may contribute to gene expression events for neuronal memory of acoustically-rich sensory cues.